Use of ivabradine for treatment of junctional ectopic tachycardia in post congenital heart surgery - Sharma, Dhruva (Indian J Thorac Cardiovasc Surg, 2020)
Cardiac surgeries especially involving crux of the heart as performed in tetralogy of Fallot (TOF) and pulmonary stenosis are mainly responsible for junctional ectopic tachycardia (JET). Diversified antiarrhythmic agents have been used in an impressive way to treat JET but showed suboptimal efficacy and varied associated adverse effects. But, ivabradine has proved as final crusader for its treatment. We report our initial experience of 4 cases in last 6 months with ivabradine in the management of postoperative JET. Encouraged by various reports and our increasing experience with ivabradine in heart failure population, we have moved to ivabradine as the first drug of choice for postoperative JET. Bradycardia was the only significant adverse effect in our series. The availability of atrial and ventricular pacing wires or at least transvenous temporary pacing should be ensured before starting ivabradine.